Internal curing of natural hydraulic lime with superabsorbent polymers. (March 2023) - Li, Yunfeng; Luo, Hongjie; Zhang, Biao; Wei, Xiaohong; Wang, Fen; Wang, Wenke; Liu, Pengwei; Zhu, Jianfeng
Abstract: This paper studied the swelling behavior of two types of superabsorbent polymer (SAP) and their effect on the properties of natural hydraulic lime (NHL2). The rheology of NHL2 paste depends on the water absorption kinetics of SAP. Although chemically different, SAPs can promote hydration and Carbonation of NHL2. Moreover, SAPs can compensate for autogenous shrinkage. The hydration products of NHL showed a gradient growth on the SAP surface and formed an NHL/SAP interface transition zone. However, SAP will leave pores that provide access for CO2 to enter the matrix. As a result, the porosity increased, reducing the compressive strength. Graphical Abstract: ga1